Disentangling the effects of age and APOE on neuropathology and late life cognitive decline - Yu, Lei (2013)
Age and APOE are the most robust risk factors for dementia and cognitive decline, but the underlying neurobiology remains unclear. We examined the extent to which the hallmark pathologies of Alzheimer’s disease, Lewy body disease, and cerebrovascular diseases account for the association of age and APOE with decline in episodic memory versus non-episodic cognitive abilities. Up to 20 waves of longitudinal cognitive data were collected from 858 autopsied participants in two ongoing clinical-pathologic cohort studies of aging. Neuropathologic examinations quantified measures of beta amyloid plaque (Aβ), mesial temporal and neocortical neurofibrillary tangles, macro- and microinfarcts, and neocortical Lewy bodies. Random coefficient models estimated person-specific slopes of decline in episodic memory and non-episodic cognition. Path analysis examined the relation of age, APOE and the six pathologic indices to the slopes of cognitive decline. The effect of age on decline in episodic memory was mediated by Aβ, mesial temporal and neocortical tau tangles, as well as macroscopic infarcts; age on decline in non-episodic cognition was mediated by Aβ, neocortical tangles, and macroscopic infarcts. The effect of APOE on decline in episodic memory was mediated by Aβ, mesial temporal and neocortical tangles, as well as neocortical Lewy bodies; APOE on non-episodic cognition was mediated by Aβ, neocortical tangles and neocortical Lewy bodies. There were no direct effects of age and APOE on decline after accounting for these pathologic pathways.